Evaluation of the relationship of picoplankton and viruses to environmental variables in a lagoon system (Çakalburnu Lagoon, Turkey). Issue 3 (16th March 2018) - Yucel-Gier, Guzel; Kacar, Aslı; Gonul, L. Tolga; Pazi, Idil; Kucuksezgin, Filiz; Erarslanoglu, Neslihan; Kubra Toker, S.
ABSTRACT: Lagoons are defined as wetlands separated from the sea coasts on which they are located and sit between continental and marine aquatic ecosystems. Çakalburnu Lagoon is a coastal wetland on the southern side of the Bay of İzmir. Microorganisms, which are quite sensitive to changes occurring in environmental factors, are commonly used to determine the impact of environmental effects on the functioning of the ecosystem. In this study, variations in the abundance and biomass of picoplankton ( Synechococcus spp. and bacteria) and the abundance of viruses, which identify the ecological productivity of the food chain, were seasonally examined by epifluorescence microscopy. Moreover, the microbial abundance and biomass relation over time between the physical and chemical parameters was evaluated. According to our results, the maximum abundance of Synechococcus spp. and viruses was 6.7 × 10 4 cell/ml and 9.9 × 10 8 cell/ml in the summer, respectively. Otherwise, the highest level of bacteria was measured at 3.6 × 10 7 cell/ml in the spring. Based on the principal component analysis and Pearson correlation analysis results, we concluded that total suspended solids, Chl- a, particulate organic carbon and particulate organic nitrogen were the major parameters influencing the observed variability of the lagoon system. Overall, to protect and improve the ecological and microbiological quality of aquatic systems such as lagoons, the necessary monitoring and measurement studies should be conducted in these sensitive areas.